BUSINESS COOPERATION BETWEEN INDONESIA AND VIETNAM - Nguyen Ngoc (SAMPURASUN, 2016)
Currently, Indonesia has the fourth largest population in the world, with the tenth largest economy by purchasing power, and Indonesia is part of the G-20. Indonesia has an economic long-term developmentto be implemented between 2005 and 2025. The plan is divided into five-year period, each of them with a different sector development priorities. Regarding business climate, although generally positive, Indonesia still continues to experience challenges of uncertainty and lack of infrastructures. However, the Investment Coordinating Board has established one service called Pelayanan Terpadu Satu Pintu (PTSP) that provides business licenses, and there are further regulation for more openness regarding businesses implementations. Vietnam on the other hand has a development success story.The political and economic reform named (Doi Moi) was launched in 1986 and has transformed the country from one of the world's poorest countries, with a per capita income of about $ 100, to a medium income country in a century, with revenues of more than $ 2,000 per capita by the end of 2014. the government has recently paid increasing attention to improve the business environment, with two resolutions that was published in March 2014 and March 2015, established concrete measures to remove obstacles to business creation in Vietnam, with the goal of achieving a business environment comparable to the average of the ASEAN-6 countries group. Both of these countries: Indonesia and Vietnam have been running back ever ties relations, they have now become a means of fostering mutual understanding and strengthened cooperation between them, which is carried on in various sectors of thei reconomy. This paper will discuss about the business relationship between the Republic of Indonesia at the Socialist Republic of Vietnam.